The associations between motivational climate, basic psychological needs and dropout in volleyball – A comparison across competitive levels. Issue 3 (4th March 2023) - Elsborg, Peter; Appleton, Paul; Wikman, Johan M.; Nielsen, Glen
ABSTRACT: The purpose of this study was to investigate the importance of motivational climate for the satisfaction of psychological needs and dropout in recreational, intermediate and elite volleyball. Seven thousand nine hundred thirty six volleyball players from all 321 volleyball clubs across Denmark were invited to participate in the study. Three thousand three thirty answered the questionnaire and 2150 were included in the analysis. Dropout from Volleyball was measured as the proportion of players that had stopped playing volleyball over the last year. The coach-created motivational climate was measured using the Motivational Climate Scale for Youth Sports. The satisfaction of players' psychological needs was measured using an adapted version of the basic psychological needs in exercise scale. The psychometric scales were validated and showed good model fit. For volleyball players of all levels, the degree of mastery climate predicted the satisfaction of the players' basic psychological needs satisfaction during volleyball which was, in turn, associated with lower dropout rates. Performance climate had a weak negative association with the satisfaction of psychological needs on the intermediate level only. When adjusting the models for the negative association between performance climate and mastery climate this negative association became nonsignificant and a weak positive association to needs satisfaction emerged for players at the elite level. Findings confirm that the coach-created mastery climate in volleyball teams is important for the satisfaction of players' basic psychological needs and continuation within the sport across the recreational, intermediate and elite levels. Highlights: Coach-created mastery climate in volleyball teams was positively associated with the satisfaction of the players' basic psychological and negatively associated with dropout. These associations between coach created climate, need satisfaction and dropout were similar across different sporting levels. Performance orientation had little influence and seemed mainly problematic if it was at the expense of mastery climate.